First-year dynamics of the anaerobic microbiome and archaeome in infants’ oral and gastrointestinal systems - Charlotte J. Neumann; Rokhsareh Mohammadzadeh; Pei Yee Woh; Tanja Kobal; Manuela-Raluca Pausan; Tejus Shinde; Victoria Haid; Polona Mertelj; Eva-Christine Weiss; Vassiliki Kolovetsiou-Kreiner; Alexander Mahnert; Christina Kumpitsch; et al. (mSystems)
ABSTRACT Recent research provides new insights into the early establishment of the infant gut microbiome, emphasizing the influence of breastfeeding on the development of gastrointestinal microbiomes. In our study, we longitudinally examined the taxonomic and functional dynamics of the oral and gastrointestinal tract (GIT) microbiomes of healthy infants (n = 30) in their first year, focusing on the often-over-looked aspects, the development of archaeal and anaerobic microbiomes. Breastfed (BF) infants exhibit a more defined transitional phase in their oral microbiome compared to non-breastfed (NBF) infants, marked by a decrease in Streptococcus and the emergence of anaerobic genera such as Granulicatella. This phase, characterized by increased alpha-diversity and significant changes in beta-diversity, occurs earlier in NBF infants (months 1–3) than in BF infants (months 4–6), suggesting that breastfeeding supports later, more defined microbiome maturation. We demonstrated the presence of archaea in the infant oral cavity and GIT microbiome from early infancy, with Methanobrevibacter being the predominant genus. Still, transient patterns show that no stable archaeome is formed. The GIT microbiome exhibited gradual development, with BF infants showing increased diversity and complexity between the third and eighth months, marked by anaerobic microbial networks. NBF infants showed complex microbial co-occurrence patterns from the start. These strong differences between BF and NBF infants’ GIT microbiomes are less pronounced on functional levels than on taxonomic levels. Overall, the infant microbiome differentiates and stabilizes over the first year, with breastfeeding playing a crucial role in shaping anaerobic microbial networks and overall microbiome maturation.IMPORTANCEThe first year of life is a crucial period for establishing a healthy human microbiome. Our study analyses the role of archaea and obligate anaerobes in the development of the human oral and gut microbiome, with a specific focus on the impact of breastfeeding in this process. Our findings demonstrated that the oral and gut microbiomes of breastfed infants undergo distinct phases of increased dynamics within the first year of life. In contrast, the microbiomes of non-breastfed infants are more mature from the first month, leading to a steadier development without distinct transitional phases in the first year. Additionally, we found that archaeal signatures are present in infants under 1 year of age, but they do not form a stable archaeome. In contrast to this, we could track specific bacterial strains transitioning from oral to gut or persisting in the gut over time.